2011
DOI: 10.1038/srep00017
|View full text |Cite
|
Sign up to set email alerts
|

Multibudded tubules formed by COPII on artificial liposomes

Abstract: COPII-coated vesicles form at the endoplasmic reticulum for cargo transport to the Golgi apparatus. We used in vitro reconstitution to examine the roles of the COPII scaffold in remodeling the shape of a lipid bilayer. Giant Unilamellar Vesicles were examined using fast confocal fluorescence and cryo-electron microscopy in order to avoid separation steps and minimize mechanical manipulation. COPII showed a preference for high curvature structures, but also sufficient flexibility for binding to low curvatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 30 publications
(51 reference statements)
4
98
0
1
Order By: Relevance
“…Our conclusion is that agarose vesicles should not be employed for instance when extracting membrane properties from vesicle deformation (4,35), pore formation by membrane active molecules (8,42,43), protein-induced membrane curvature (44)(45)(46), initial steps in membrane solubilization by detergents (47,48), and vesicle reshaping during changes in the phase state of the bilayer (7,49). On the other hand, studies focusing on membrane properties such as lateral mobility of membrane components and phase separation, or membrane protein reconstitution might still profit from the use of agarose-GUVs.…”
Section: Discussionmentioning
confidence: 96%
“…Our conclusion is that agarose vesicles should not be employed for instance when extracting membrane properties from vesicle deformation (4,35), pore formation by membrane active molecules (8,42,43), protein-induced membrane curvature (44)(45)(46), initial steps in membrane solubilization by detergents (47,48), and vesicle reshaping during changes in the phase state of the bilayer (7,49). On the other hand, studies focusing on membrane properties such as lateral mobility of membrane components and phase separation, or membrane protein reconstitution might still profit from the use of agarose-GUVs.…”
Section: Discussionmentioning
confidence: 96%
“…However, coating of a membrane patch to promote curvature and concentrate cargo at the tip of a transiently produced tubule is a distinct possibility. It has been shown in vitro that COPII components can tubulate liposome membrane (Bacia et al, 2011), and it has even been suggested that COPII coat components have sufficient flexibility to form 300-nm tubular structures that can accommodate large filamentous cargo such as procollagen fibrils (Miller and Schekman, 2013). Such tubes could easily span the narrow greater-than-300-nm interface between ER and cisGolgi in plants.…”
Section: Federica Brandizzi: the Secretory Units Model For Er Proteinmentioning
confidence: 99%
“…Alternatively, TANGO1/cTAGE5 might constitute machinery that switches COPII coat assembly from small spherical vesicles to large carriers, but such a mechanism has not been explored to date. Important in this respect is the observation of tubular COPII carriers with dimensions commensurate with procollagen cargo; such tubules form, along with small vesicles, in budding reactions in vivo and in vitro (14)(15)(16). COPII-coated tubules are observed as straight-sided tubes (17), or with a beads-ona-string appearance in which regular constrictions may arise from aborted attempts at membrane fission (14,16).…”
mentioning
confidence: 99%
“…Important in this respect is the observation of tubular COPII carriers with dimensions commensurate with procollagen cargo; such tubules form, along with small vesicles, in budding reactions in vivo and in vitro (14)(15)(16). COPII-coated tubules are observed as straight-sided tubes (17), or with a beads-ona-string appearance in which regular constrictions may arise from aborted attempts at membrane fission (14,16). Whereas vesicles contain a Sec23/24 inner coat and a self-assembled Sec13/31 cage with isometric (cubic) symmetry, tubules are coated with a distinctive, close-packed Sec23/24 helical lattice and a rhomboidal Sec13/31 cage (17).…”
mentioning
confidence: 99%